Dental Education Digitalization: Virtual Reality (VR) and Augmented Reality (AR) - Kaan Orhan; Merve Onder (European Annals of Dental Sciences)
In dental education, the role of practical training is crucial. Dental students undergo numerous practical training sessions during the first three years to enhance their manual and visual skills. Technological advancements have found their place in the field of dentistry, as in every other area. Three-dimensional (3D) imaging and printing, computer-aided design and computer-aided manufacturing (CAD/CAM), artificial intelligence (AI), virtual reality (VR), and augmented reality (AR) based applications are building a significant presence in both dental education and practice. Objective and Method: Our aim in this review is to investigate the impact and significance of VR and AR in dental education. Therefore, a comprehensive literature review was conducted on the subject, and the results were evaluated and summarizedResults and Conclusions: One of the most significant advantages of AR and VR systems is their ability to facilitate manual skill acquisition and minimize errors with instant feedback. The major distinguishing feature of AR systems from VR systems in education is the absence of disconnection from reality in the former case. AR gives students the feeling of being in a real environment and guides them during dental treatment. Although AR and VR applications seem easily integrable into dental education, further research is needed for these emerging digital technologies.